Regional Strategic Groups as an Instrument for the Location’s Decisions Supporting on the Example of Food Industry - Godlewska-Majkowska, Hanna; Komor, Agnieszka (Olsztyn Economic Journal, 2016)
Process of planning the location of enterprises still lacks the method allowing for combining spatial analysis with the competitiveness analysis of the industries or their clusters, while taking into account the competitive position and competitive potential. The purpose of the study is to create a new methodical pattern in the location analysis of the company based on regional strategic groups, and to show the possibilities and limitations of the proposed tool’s application, supporting location decisions on the example of food industry companies in NUTS 2 level regions in Poland. The study included medium and large enterprises of the food industry in 2013. This paper contains an attempt of application of a modified McKinsey matrix for spatial analyses, using the investment attractiveness indexation of regions. The suggested modification of McKinsey matrix is a new proposal in this respect, while at the same time being an attempt to solve the problem of the management. Regional strategic groups analysis allows one to propose possible strategic actions for businesses, which helps to solve the problem of location management of group of companies, including regional clusters. It is worth noting that the proposed instrument also contributes to the actions of the local government units (regions), concerning the adaptation of investment offer to the needs of business entities.